SEASONAL FLUCTUATIONS IN THE SURFACE SALINITY ALONG THE COAST OF THE SOUTHERN PART OF KALIMANTAN (BORNEO) - Sjarif, Sjarmilah (Marine Research in Indonesia, 1959)
The westerly current of the Java Sea from the southeast is branched to the north, along the eastcoast of Kalimantan (Borneo) as far as Cape Mangkalihat. This current brings high saline water, over 34.0 ?, and increases the salinity along the coast of the southern part of Kalimantan, working together with the decreasing rains. In the westmonsoon, when the westward current has retreated and the easterly current from the South China Sea has developed, the northerly current along the eastcoast is replaced by a southerly current, from ,the Pacific. Under influence of the increasing rains and the large outflow of the rivers in the southern part of Kalimantan the salinity decreases rapidly, until a minimum value. This minimum is found irregularly during the diffferent months of the westmonsoon or the succeeding transition period. The lowest values are found in Sukadana Bay (29.0 ?) and off Bandjarmasin (± 24.0 ?). The further from this place, the higher the values. The maximum salinity is found during the months September and October in accordance with the minimum rainfall. The highest values are found in the eastern part of the investigated area (34.5 ?). To the west it is lower, the more it is mixed with the low-saline water of the Java Sea. The salinity in the Karimata Strait is about 33.0 to 33.5 ?.